Variability in water chemistry of the Three Gorges Reservoir, China - Wang, Hao (Heliyon, 2020)
The environmental influence of the Three Gorges Reservoir (TGR) on the Changjiang River has been widely studied since the Three Gorges Dam (TGD) began operation in 2003. However, the changes in water chemistry in the reservoir in response to damming effect variations are poorly documented in the area of this large reservoir. The results suggest that in comparison to the water chemistry before the TGR operation, the inflow concentrations of Mg(2+), K(+), Na(+) and Cl(−) increased in the TGR, and the abundance of Ca(2+) and HCO(3)(-) decreased in the inflow in the period after the TGR filling as a result of climate change and human activities in the Changjiang River basin. The ionic composition in the TGR is primarily controlled by contributions from the upstream region of the Changjiang River but was modified by the interaction between water and rocks within the TGR. The concentrations of most major ions as well as the equivalent ratios of the major ions increased in the TGR after the operation of TGD. This change yielded a 6% increase in the major ion loading downstream of the TGD. The Three Gorges area strongly contributes to the increase in ion loading in the TGR due to enhanced water and rock interactions in comparison with the period before TGD operation.